The Role of Executive Functioning in PTSD and its Treatment - Bomyea, J.; J. Lang, A. (Current Psychiatry Reviews, 2015)
The current review describes evidence for the critical role of executive functioning in the development and/or maintenance of posttraumatic stress disorder (PTSD). As part of this review, we describe associations between executive functioning, intrusive thoughts, and PTSD. Moreover, we explore evidence for the utility of cognitive training programs to improve executive functioning as a potential novel treatment approach. A model is presented that depicts how poor executive functioning and associated intrusive thoughts, in the context of unsuccessful attempt to regulate cognitions and emotions, may lead to or perpetuate PTSD symptoms.
Keywords: treatment